Synthesis and flash sintering of zirconium nitride powder. Issue 6 (24th February 2022) - Das, Suprabha; Dubois, Diego; Sozal, Md Shariful Islam; Emirov, Yusuf; Jafarizadeh, Borzooye; Wang, Chunlei; Drozd, Vadym; Durygin, Andriy; Cheng, Zhe
Abstract: Zirconium nitride (ZrN) is a transition metal nitride of great interest due to its excellent physical and chemical properties. This study aims to synthesize ZrN fine powders by a facile and low‐cost urea route that avoids the use of any solvent. ZrCl4 and urea mixtures were heat‐treated at up to 1600˚C in nitrogen gas. The products were characterized by X‐ray diffraction, scanning electron microscopy, transmission electron microscopy, energy‐dispersive X‐ray spectroscopy, and thermogravimetric analysis. The effects of different processing parameters such as metal to urea molar ratio, heat treatment temperature, and dwelling time on the product phase and stoichiometry were studied to understand the synthesis method. In addition, synthesized ZrN powder was consolidated into near fully dense single‐phase bulk ceramic with a homemade flash sintering setup. A constant DC electrical field of ∼80 V/cm and pressure of ∼14 MPa at room temperature triggered flash sintering without pre‐heating, and the entire process finished in 200 s. The composition, microstructure, density, hardness, and oxidation properties of the sintered pellet were also characterized.